FinnTwin16: A Longitudinal Study from Age 16 of a Population-Based Finnish Twin Cohort. (3rd December 2019) - Kaidesoja, Milla; Aaltonen, Sari; Bogl, Leonie H.; Heikkilä, Kauko; Kaartinen, Sara; Kujala, Urho M.; Kärkkäinen, Ulla; Masip, Guiomar; Mustelin, Linda; Palviainen, Teemu; Pietiläinen, Kirsi H.; Rottensteiner, Mirva; et al.
Abstract: The purpose of this review is to provide a detailed and updated description of the FinnTwin16 (FT16) study and its future directions. The Finnish Twin Cohort comprises three different cohorts: the Older Twin Cohort established in the 1970s and the FinnTwin12 and FT16 initiated in the 1990s. FT16 was initiated in 1991 to identify the genetic and environmental precursors of alcoholism, but later the scope of the project expanded to studying the determinants of various health-related behaviors and diseases in different stages of life. The main areas addressed are alcohol use and its consequences, smoking, physical activity, overall physical health, eating behaviors and eating disorders, weight development, obesity, life satisfaction and personality. To date, five waves of data collection have been completed and the sixth is now planned. Data from the FT16 cohort have contributed to several hundred studies and many substudies, with more detailed phenotyping and collection of omics data completed or underway. FT16 has also contributed to many national and international collaborations.